Relationship between Parenting and Self-Concept in Students with Low Learning Achievement in High School - Liranda Khaira Nisa; Taufik Taufik (Jurnal Neo Konseling, 2019)
This research is backed by the phenomenon of low self-concept students, such as lack of understanding and self-acceptance, lack of personal circumstances such as the advantages and disadvantages that exist on him, many students do not know the talent and interest The students ' inability to develop their own skills. One of the low causes of student self-concept is alleged due to parenting patterns. This research aims to test the relationship of foster parents with the concept of student self. This research is a correlational descriptive type study with quantitative methods. The samples in this study were as many as 138 students who had low learning achievements consisting of classes XI and XII. Data collection instruments are a scaled poll of a variable's parenting pattern and self-concept. Data is used in the Pearson product moment formula with the program Statical Product and Service Solution (SPSS) version 20.0 The results reveal that there is a significant positive relationship between the foster parents ' pattern of self-concept Students.